Bacteriophages Perspectives and Future - Savva, Renos (IntechOpen, 2020)
Bacteriophages are viruses that utilise bacterial cells as factories for their own propagation and as safe havens for their genomic material. They are capable of equipping bacteria with properties that bestow environmental advantages. They are also capable of specifically and efficiently killing bacteria.Bacteriophages are resilient in a wide diversity of environments, presumed to be as ancient as life itself, and are estimated to be the most numerous biological entities on the planet. Their overarching capacity to survive via molecular adaptation is supported by an arsenal of encoded enzymatic tools, which also enabled biotechnology. This volume includes contributions that describe bacteriophages as nanomachines, genetic engineers, and also as medicines and technologies of the future, including relevant production and process issues.